Penerapan Sistem Fuzzy Tsukamoto Dalam Memperkirakan Hasil Produksi Padi - Lena Sapura; Agiffuddinsyah Sinaga; Firdaus Siahaan (LPPM STIKOM Tunas Bangsa, 2020)
Plantations are all activities that commercialize certain plants on the soil and / or other growing media in suitable ecosystems; process and market the goods and services produced by these plants, with the help of science and technology, capital and management to create prosperity for plantation businesses and the community. In ordinary or more dominant plantations, rice fields with sufficient yields and even processing with a fairly short period of time, especially in rice. Rice is the main or basic need and source of calories for humans. Factors that affect rice production include land, seeds, weather, and fertilizer, these factors clearly affect the quality and amount of production produced by farmers. The fuzzy logic method applies Tsukamto's fuzzy inference system in estimating rice production with the variables that influence it. The research objective is to estimate how much rice production with the Tsukamoto method of fuzzy inference using AND operations based on land variables, rice seed material, fertilizer, and the amount of production.